Źródła do dziejów dzwonów z terenu obecnego powiatu zielonogórskiego w Glockenarchiv w Norymberdze = Zielona Góra's bells' history - as documented by Glockenarchiv in Nuremberg - Górski, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Bells, being movable monuments, relatively often change their location. Many of them have scant documentation. Any information including their looks or a description of their inscriptions is, therefore, of great value.
Keywords: kampanologia; dzwony - rekwizycja; Glockenarchiv; Norymberga; źródła historyczne